Avaliação dos impactos socioeconômicos gerados com a implantação do campus da universidade federal rural do semi-árido no município de angicos-rn. - Rocha, Alexandre Miranda (Universidade Federal Rural do Semi-Árido, 2019)
Through REUNI, which promoted the restructuring of existing IFES and the creation of new ones in the interior of the country, together with the application of ENEM and SISU, they enabled young people and adults to enter higher education, the vast majority of which come from families with lower incomes 1,5 minimum wages, culminating in the availability of society's involvement with the new graduates, who contribute to the emerging economies of small and medium-sized cities where these Institutions are present, providing their maintenance through diversified programs and scholarships for these potential individuals to complete their work. graduation and perfect for the job or educational market. Through an evaluative approach on the effective participation of an IFES to a municipality in relation to its influence on economic, social, educational, environmental and infrastructure aspects motivate the study developed on this participation and its influence on the locality of Angicos/RN. implementation of the UFERSA Campus in 2009. Given this scenario, the socioeconomic impacts generated by the presence of the academic community as verified in the city come to light, which becomes the main objective of this research, thus describing the contributions of this institution and the changes generated by the dynamics and its modifying agents. This is a research with qualitative and quantitative approach, using interviews through questionnaires with objective questions that were applied to 4 distinct groups of interviewees (students, teachers, administrative and laboratory technicians and outsourced employees and residents surrounding the Campus UFERSA Angicos/RN) that are directly and indirectly influenced by the actions taken by the Institution, direct observation, documentary and bibliographic research and the use of photographic records. Whose analysis can visualize the institution's active participation in the locality, recognition of the interviewees regarding its participation and especially the visualization of the real socioeconomic impact generated through the financial participation represented by values close to those collected by the municipality through Union transfers to maintain the infrastructure, sometimes criticized for the lack of infrastructure in the areas of urbanization, health and safety under the responsibility of the municipal and state authorities. In addition, actions aimed at promoting the development of the region through the active participation of government levels (municipal, state and federal), with the active participation of the local community and mainly IFES, were analyzed and proposed through the objective of analyzing As a deployment station it can promote significant changes to the reality of the municipality in recent years and its responsibility for them as the idealizing agent of change and main contributor to development. Whose study was based on the visualization of changes presented in the last years based on the investment passed by the modifying agents coming from the Institution, besides the application of questionnaires to the students, teachers, administrative technicians, outsourced people and the surrounding community, trying to exemplify and answer on the direct and indirect influence of the university campus on local reality through territorial expansion, housing growth, economic development and employment niches with or without professional registration and the educational development of the region with the training of qualified professionals.
Keywords: Abismo social; Desenvolvimento econômico; Educação superior; Preservação ambiental; Responsabilidade social; Social abyss; Economic development; College education; Environmental preservation; Social responsability; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA